Role of thoracic ultrasonography in pleurodesis pathways for malignant pleural effusions (SIMPLE): an open-label, randomised controlled trial. Issue 2 (February 2022) - Psallidas, Ioannis; Hassan, Maged; Yousuf, Ahmed; Duncan, Tracy; Khan, Shahul Leyakathali; Blyth, Kevin G; Evison, Matthew; Corcoran, John P; Barnes, Simon; Reddy, Raja; Bonta, Peter I; Bhatnagar, Rahul; et al.
Summary: Background: Pleurodesis is done as an in-patient procedure to control symptomatic recurrent malignant pleural effusion (MPE) and has a success rate of 75–80%. Thoracic ultrasonography has been shown in a small study to predict pleurodesis success early by demonstrating cessation of lung sliding (a normal sign seen in healthy patients, lung sliding indicates normal movement of the lung inside the thorax). We aimed to investigate whether the use of thoracic ultrasonography in pleurodesis pathways could shorten hospital stay in patients with MPE undergoing pleurodesis. Methods: The Efficacy of Sonographic and Biological Pleurodesis Indicators of Malignant Pleural Effusion (SIMPLE) trial was an open-label, randomised controlled trial done in ten respiratory centres in the UK and one respiratory centre in the Netherlands. Adult patients (aged ≥18 years) with confirmed MPE who required talc pleurodesis via either a chest tube or as poudrage during medical thorascopy were eligible. Patients were randomly assigned (1:1) to thoracic ultrasonography-guided care or standard care via an online platform using a minimisation algorithm. In the intervention group, daily thoracic ultrasonography examination for lung sliding in nine regions was done to derive an adherence score: present (1 point), questionable (2 points), or absent (3 points), with a lowest possible score of 9 (preserved sliding) and a highest possible score of 27 (complete absence of sliding); the chest tube was removed if the score was more than 20. In the standard care group, tube removal was based on daily output volume (per British Thoracic Society Guidelines). The primary outcome was length of hospital stay, and secondary outcomes were pleurodesis failure at 3 months, time to tube removal, all-cause mortality, symptoms and quality-of-life scores, and cost-effectiveness of thoracic ultrasonography-guided care. All outcomes were assessed in the modified intention-to-treat population (patients with missing data excluded), and a non-inferiority analysis of pleurodesis failure was done in the per-protocol population. This trial was registered with ISRCTN, ISRCTN16441661. Findings: Between Dec 31, 2015, and Dec 17, 2019, 778 patients were assessed for eligibility and 313 participants (165 [53%] male) were recruited and randomly assigned to thoracic ultrasonography-guided care (n=159) or standard care (n=154). In the modified intention-to-treat population, the median length of hospital stay was significantly shorter in the intervention group (2 days [IQR 2–4]) than in the standard care group (3 days [2–5]; difference 1 day [95% CI 1–1]; p<0·0001). In the per-protocol analysis, thoracic ultrasonography-guided care was non-inferior to standard care in terms of pleurodesis failure at 3 months, which occurred in 27 (29·7%) of 91 patients in the intervention group versus 34 (31·2%) of 109 patients in the standard care group (risk difference −1·5% [95% CI −10·2% to 7·2%]; non-inferiority margin 15%). Mean time to chest tube removal in the intervention group was 2·4 days (SD 2·5) versus 3·1 days (2·0) in the standard care group (mean difference −0·72 days [95% CI −1·22 to −0·21]; p=0·0057). There were no significant between-group differences in all-cause mortality, symptom scores, or quality-of-life scores, except on the EQ-5D visual analogue scale, which was significantly lower in the standard care group at 3 months. Although costs were similar between the groups, thoracic ultrasonography-guided care was cost-effective compared with standard care. Interpretation: Thoracic ultrasonography-guided care for pleurodesis in patients with MPE results in shorter hospital stay (compared with the British Thoracic Society recommendation for pleurodesis) without reducing the success rate of the procedure at 3 months. The data support consideration of standard use of thoracic ultrasonography in patients undergoing MPE-related pleurodesis. Funding: Marie Curie Cancer Care Committee